Tribological Mechanism in Machining and Its Use - Vasilko, Karol (Manufacturing Technology Journal, 2018)
It is a well-known fact that during cutting there occurs an extremely high degree of chip plastic deformation [1,4,5,11] These deformation structures require attention as they influence technical and economical results of cutting (cutting forces, quality of machined surface, tool wear, cutting temperature) [8,9,15,21]. The paper analyses the options of influencing the deformation field in chip with the aim to improve cutting proces.
Keywords: machining; plastic deformation; chip forming; cutting force